1970
DOI: 10.1099/00221287-61-3-335
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies on Walls Synthesized by Candida utilis Protoplasts

Abstract: SUMMARYProtoplasts of Candida utilis obtained by treatment with helicase built a new wall in a liquid medium. The spherical protoplast was converted to a tubular form which later changed to an ellipsoidal yeast. Walls isolated at different stages of regeneration were analysed. Glucan (42 to 48 %), mannan (25 to 31 %) and protein (8 to 9 %) were the main constituents of walls of normal and completely regenerated ellipsoidal forms. Walls of the tubular forms differed markedly by having a high content of chitin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Preparations of the residual thin fibrils treated for 7 days with commercial chitinase showed almost complete removal when examined under the conditions described, indicating the chitinous nature of these fibrils. These results agree with the previous chemical characterization of such extracted fractions [8] and also the report [10] in which c~-glucan from Aspergillus niger and Polyporus betulinus and commercial chitin samples showed similar ultrastructure to these preparations.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Preparations of the residual thin fibrils treated for 7 days with commercial chitinase showed almost complete removal when examined under the conditions described, indicating the chitinous nature of these fibrils. These results agree with the previous chemical characterization of such extracted fractions [8] and also the report [10] in which c~-glucan from Aspergillus niger and Polyporus betulinus and commercial chitin samples showed similar ultrastructure to these preparations.…”
Section: Resultssupporting
confidence: 93%
“…Chemical characterization of the different fractions extracted from hyphal walls of another strain of A. bisporus has been recently carried out [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamaya (10) reported that lysozyme was fungicidal for several species of Candida including C. albicans. Lysozyme was found to interfere with reversion of helicase-prepared protoplasts of C. utilis to complete cells (16). Schmidt (21) showed that lysozyme inhibited hyphal growth and induced degeneration of germ tubes or the release of cytoplasmic contents from conidia of Peronospora tabacina.…”
Section: Discussionmentioning
confidence: 99%